BIOCHEMICAL PARAMETERS IN THE BLOOD OF PREGNANT SHEEP AGAINST THE BACKGROUND OF KETONURIA [Text] - Avdeenko, V.S.; Sengaliev, E. M.; Kereyev, A. K. (Science and education№1, 2018)
The metabolic parameters traditionally used in the diagnostic algorithm in pregnant sheep in subclinical ketosis are in many cases less sensitive and specific than the «lipid peroxidation-antioxidant protection» system parameters. In the future, the material obtained in this study should be considered when studying the problem of subclinical and clinical ketosis of pregnant sheep as the concept of development of dysfunction «LPO-AOD» system for this metabolic disease.Метаболические параметры, которые традиционно используются в диагностическом алгоритме у суягных овец при субклиническом кетозе в ряде случаев отличаются меньшей чувствительностью и специфичностью, чем показатели системы «перекисное окисление липидов – антиоксидантная защита». В перспективе полученный материал в данной работе следует учитывать при изучении проблемы субклинический и клинический кетоз суягных овец, как концепцию развития нарушения функционирования системы «ПОЛ-АОЗ» при данной метаболической патологии.
Keywords: рк; отечественное издание; научный журнал; периодическое издание; ветеринария; метаболическая патология